Views About Scientific Inquiry: A Study of Students' Understanding of Scientific Inquiry in Grade 7 and 12 in Sweden. Issue 2 (23rd February 2022) - Gyllenpalm, Jakob; Rundgren, Carl-Johan; Lederman, Judith; Lederman, Norman
ABSTRACT: This paper analyses data from the Swedish sample of the international VASI (Views about scientific inquiry) study (Lederman et al. [2019]. An international collaborative investigation of beginning seventh grade students' understandings of scientific inquiry: Establishing a baseline. Journal of Research in Science Teaching . Published online. https://doi.org/10.1002/tea.21512 ). Understandings about scientific inquiry involve knowledge about the processes of inquiry, and are not the same as being able to do inquiry although these are related domains. This paper focuses on what students know about scientific inquiry and what impact school science may have on this knowledge. Data were collected using the VASI instrument developed previously and was administered to 126 students at the beginning of year seven and 145 students at the end of year 12 in a cross-sectional design. Results indicate that the majority of students do not have an informed understanding of key aspects of scientific inquiry in either grade. Although students in year 12 are more informed, the average is still less than 50% as measured by the VASI and with a large spread.